pereSTROIKA - umBAU einer Wohnung . Perestroika - Reconstruction a Flat - Büchner, Christiane (Büchner, Tobias, 2008)
Verzio FF Once the seat of the Russian Empire, the historic center of St. Petersburg is up for sale. Having had its architectural jewels hacked up into kommunalka's during the Communist era, the city is now experiencing a boom of reconstruction, where communal property promises capitalist-sized profits. In one flat on Marat Street, each of the four rooms is inhabited by a different family, all of whom share the bathroom and kitchen. When one owner decides to put her room on the market, she must also convince the others to sell. Enter the self-interested real estate agents and impatient buyers, and a frenzied unraveling of the already tenuous relationships ensues. As witness to the many intrigues involved in the sale, filmmaker Christiane Büchner brings us along for a sardonic ride with intractable neighbors through the cramped quarters, peeling-paint hallways, and water-damaged ceilings of Russia's new economy, which in the end head-butts against its Byzantine past.